2019
DOI: 10.3390/f10040353
|View full text |Cite
|
Sign up to set email alerts
|

Site Type Effect on Litter Decomposition Rates: A Three-Year Comparison of Decomposition Process between Spoil Heap and Forest Sites

Abstract: Research Highlights: Direct comparison of leaf litter decomposition rates between harsh soil conditions of degraded lands and adjacent “closer to natural” forest areas has not been done before. Background and Objectives: We aimed to fill this knowledge gap by determining the differences in amounts of carbon and nitrogen released by species-specific litter depending on decomposition rates in various stand and habitat conditions, which enables selection of the most ecologically and economically appropriate (for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 61 publications
2
7
0
Order By: Relevance
“…Similar to our findings, a litterbag study in a pine forest of Central Poland found that pronounced N immobilization occurred in undisturbed stands compared with disturbed ones [62]. By the end of our experiment, the N amount in litterbags was 115% of the initial N mass at the control site and 149% of the initial N mass at the burned site.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to our findings, a litterbag study in a pine forest of Central Poland found that pronounced N immobilization occurred in undisturbed stands compared with disturbed ones [62]. By the end of our experiment, the N amount in litterbags was 115% of the initial N mass at the control site and 149% of the initial N mass at the burned site.…”
Section: Discussionsupporting
confidence: 91%
“…The small biomass and low degree of cover by the herb layer most probably results from the large biomass of litter under P. sylvestris (Rawlik et al, 2018), which limits plant growth and germination. Another explanation may be lower light levels that reach the forest floor under P. sylvestris in comparison to B. pendula and A. glutinosa (Horodecki & Jagodziński, 2019). In addition, concentrations of alkaline cations under P. sylvestris on sandy sites were the lowest (for Ca, less than half as high), while Fe content was higher than in the neighbouring forest stands of B. pendula .…”
Section: Discussionmentioning
confidence: 99%
“…Spoil heaps created as a result of open‐pit lignite mining allow observation of initial soil‐forming processes in soil‐less areas (Hendrychová, 2008; Horodecki & Jagodziński, 2019; Prach, 2013). Forest research conducted relatively recently on wooded plots under pure stands of 14 tree species about 30 years old, showed significant effects of tree species on variation in site conditions, as well as species diversity of plants, fungi, and animals (Hobbie et al, 2006; Mueller et al, 2016; Reich et al, 2005; Skorupski, Jagodziński, Żytkowiak, & Karolewski, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In different periods of forest succession, profound changes in soil habitat caused by differences in aboveground vegetation affect the leaf litter decomposition (Forest et al., 2013 ; Prescott et al., 2000 ). Previous research demonstrated that leaf litter decomposition may be influenced by litter quality, soil physicochemical properties, and/or biological factor adjustments (Bray et al., 2012 ; García‐Palacios et al., 2016 ; Horodecki & Jagodziński, 2019 ; Polyakova & Billor, 2008 ). In this study, we found that leaf litter decomposition was significantly different in the primary Korean pine forest and secondary broad‐leaved forest.…”
Section: Discussionmentioning
confidence: 99%